The Influence of Room Prices and Promotion Costs on Hotel Room Occupancy Rates in Palopo City, South Sulawesi - Wayan Suardana; Muhadjir Suni; Masri Ridwan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
Hotel competition in South Sulawesi Province in 2018 has increased. This study aims to: determine the price of hotel rooms in the city of Palopo, South Sulawesi Province, find out how the cost of hotel promotions in the City of Palopo, South Sulawesi Province, find out whether the room price and promotion costs have a significantly positive effect on hotel room occupancy rates in Palopo City, South Sulawesi Province. This type of research is descriptive quantitative research. Data collection techniques used are the method of observation, documentation techniques and questionnaires. The results showed that of 17 Hotels / Pensions / Villas in Palopo City, South Sulawesi Province, the room occupancy rate was on average 27%. Promotion fee is Rp. 17,368, - per room. Of the two regression coefficients possessed by the two independent variables, the two independent variables (X1) namely room price and promotion costs (X2) have a significant positive effect on the occupancy rate of the room (Y).